Microfluidic-assisted toxicity studies of jet fuels on environmental microorganisms – Towards new lab-on-a-chip sensing applications. (30th November 2022) - (Podwin), Agnieszka Krakos; Janicka, Anna; Molska, Justyna; Zawiślak, Maciej; Lizanets, Danylo; Białecki, Tomasz; Gawron, Bartosz; Suchocki, Tomasz
Highlights: All-glass lab-on-chip with software-enhanced metrological parametrization of cells behaviour is shown. Toxin-to-cell effects on-chip with a view to selected jet fuels: Jet A-1 and Jet A-1 + HEFA are measured. Cells' mobility decreased by 80 % and 100 % after 20 min exposure to the jet fuels. Chromatography analysis of VOCs and BTEX group was conducted. Addition of HEFA-type hydrocarbons resulted in BTEX group concentration increase by 61% Abstract: In this paper, a lab-on-a-chip (LOC) for cellular studies with software-enhanced metrological parametrisation of toxin-to-cell effects on-chip is shown. A special design of LOC is proposed herein whose performance prior to use was confirmed utilising numerical simulations based on a laminar exhaust microflow module. Model microorganisms – Euglena gracilis – were used as a bioindicator to evaluate the toxicity of jet fuels, i.e. Jet A-1 and Jet A-1 + HEFA (Hydroprocessed Esters and Fatty Acids). Apart from the biological results that show notable cell degradation for both of the fuels after 20 min of exhaust exposure (e.g. mobility decrease by 80 % and 100 % for Jet A-1 and Jet A-1 + HEFA), interesting outcomes were also obtained in an exhaust gas chromatography analysis, being in strong correlation with the observed euglena colony behaviour. The major focus was put herein on the concentration of VOCs (Volatile Organic Compounds) and BTEX (Benzene, Toluene, Ethylbenzene and Xylene isomers). Although the sum of volatile hydrocarbon compounds in the exhaust gas decreased due to the addition of HEFA-type hydrocarbons to the fuel, the concentration of the most toxic, BTEX group, was increased about two times compared to the standard Jet A-1. On that basis, our preliminary tests show that further research in this regard is required, in the context of both the toxin-to-cell impact and its direct correlation with the fuel composition.